2014
DOI: 10.1063/1.4903274
|View full text |Cite
|
Sign up to set email alerts
|

How does a thermal binary crystal break under shear?

Abstract: When exposed to strong shearing, the particles in a crystal will rearrange and ultimately, the crystal will break by forming large nonaffine defects. Even for the initial stage of this process, only little effort has been devoted to the understanding of the breaking process on the scale of the individual particle size for thermalized mixed crystals. Here, we explore the shear-induced breaking for an equimolar two-dimensional binary model crystal with a high interaction asymmetry between the two different speci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 94 publications
0
4
0
Order By: Relevance
“…The above work was accomplished using a new 2D Stokesian simulation methodology that correlates interparticle interactions with the interfacial colloidal microstructure deformation due to surface flow for monodispersed charged microparticles at a fluid–fluid interface. In this methodology, interparticle interactions at fluid–fluid interfaces have been assumed to stem from dipolar repulsion between interfacial particles as well as capillary attraction caused by interfacial deformations, which differs significantly from the bulk of the literature which uses various repulsive or LJ potentials. , Furthermore, using 2D Stokesian dynamics, an underlying flow can be subjected to the entire interface, rather than through movement of the walls alone. , Therefore, this simulation methodology is applicable to capturing particle movements and microstructural formations and deformations at fluid–fluid interfaces subjected to different known flow fields.…”
Section: Discussionmentioning
confidence: 99%
“…The above work was accomplished using a new 2D Stokesian simulation methodology that correlates interparticle interactions with the interfacial colloidal microstructure deformation due to surface flow for monodispersed charged microparticles at a fluid–fluid interface. In this methodology, interparticle interactions at fluid–fluid interfaces have been assumed to stem from dipolar repulsion between interfacial particles as well as capillary attraction caused by interfacial deformations, which differs significantly from the bulk of the literature which uses various repulsive or LJ potentials. , Furthermore, using 2D Stokesian dynamics, an underlying flow can be subjected to the entire interface, rather than through movement of the walls alone. , Therefore, this simulation methodology is applicable to capturing particle movements and microstructural formations and deformations at fluid–fluid interfaces subjected to different known flow fields.…”
Section: Discussionmentioning
confidence: 99%
“…The results on the single-component Lennard-Jones crystal motivate us to consider a system less prone to re-crystallization. Pre- vious studies on glass-forming systems have shown that a nonadditive 2:1 mixture of large and small Lennard-Jones particles is highly stable to crystallization 14 , probably due, firstly, to the vicinity of its stoichiometry to the eutectic point of the mixture 31 and secondly to the fact that binary crystals fail differently under shear compared to one-component crystals 32 . The mixture crystallizes into the Al 2 Cu arrangement, whose unit cell is characterized by spindles of small particles surrounded by square rings of large particles, forming a bicapped square antiprism 33 .…”
Section: Two-component Lennard-jones Crystalmentioning
confidence: 99%
“…Further, the material response to shear is intimately connected to the nonequilibrium dynamics of the constituent elements, that have been the subject of recent research with non-Brownian particles, 13,14 polymer-, 15 active bacteria-, 16 and colloidal suspensions in amorphous, [17][18][19] fluid-, 20,21 as well as crystalline states. [22][23][24][25] Colloidal suspensions under external fields have proven to be a powerful test bed system, that is used to study the role of channel geometry 9,17,26 hydrodynamic interactions, 24,27 frictional interparticle contact and lubrication, 28,29 as well as plastic events, [30][31][32] to cite a few. Key advantages of using colloidal particles are the possibilities to directly visualize the particle dynamics via video microscopy, and to tune the pair interactions using external fields.…”
Section: Introductionmentioning
confidence: 99%